Effect of Helicobacter pylori infection on intragastric urea and ammonium concentrations in patients with chronic renal failure. Issue 6 (June 1993) - Neithercut, W D; Rowe, P A; el Nujumi, A M; Dahill, S; McColl, K E
Abstract : AIM--To assess the value of measuring the gastric juice urea:ammonium ratio in detecting Helicobacter pylori infection in patients with chronic renal failure. METHODS--Twenty three (12 men) patients with established chronic renal failure and dyspepsia were studied. Gastric juice (2 ml) was aspirated during endoscopy to measure urea and ammonium. The upper gastrointestinal tract was routinely inspected and two antral biopsy specimens obtained. The 14C-urea breath test was conducted within 14 days of endoscopic examination to determine H pylori antibody response. RESULTS--The median (range) serum urea concentration in 11 patients with renal failure and H pylori infection was similar to that in 12 without H pylori infection. The median gastric juice urea concentration in subjects with infection was lower than that in the subjects without infection (p < 0.01). The median gastric juice ammonium concentration in subjects with the infection was higher compared with subjects without infection (p < 0.01). There was an overlap of the urea and ammonium concentrations in gastric juice from both H pylori positive and negative subjects. The urea:ammonium ratio was 0.16 (0.01-1.11) for subjects with H pylori compared with 1.63 (1.0-18.9) in subjects without infection (p < 0.001). CONCLUSION--The urea:ammonium ratio differentiated both groups, with the exception of one false negative result. The urea:ammonium ratio proved almost as effective in identifying the presence of H pylori infection in subjects with chronic renal failure as it had in subjects with normal renal function.